Desain Simulasi dan Analisa Closed Loop Boost Converter Terintegrasi Solar PV Berbasis PID - Rahma Nur Amalia; Wijaya Kusuma (Politeknik Negeri Malang, 2023)
The tendency for the price of using solar PV (photovoltaic) to become cheaper means that the portion of the use of this solar energy source is encouraged to be larger along with the addition of the portion of renewable energy (EBT) generators based on PLN's 2021-2030 Electricity Supply Business Plan (RUPTL). As a step to mitigate this problem, a power electronics circuit application is needed in the form of a boost converter or what can be called a step-up DC-DC converter. In this study, the boost converter design modeling is made a closed loop. There is feedback by adding a PID controller to adjust the duty cycle as a function of switching on or off MOSFET so that the output voltage is as desired (setpoint) and adjusts to needs of load. Open-loop design modeling is also included as a comparison. The design stage begins with determining the circuit design, calculating component specifications, and simulating using MATLAB R2013a software and hardware implementation. From the test results, it was found that the boost converter can increase the solar PV voltage varies (17.34-19.13 Volts). In the closed loop boost converter circuit with a constant load of 129.96 Ω with varying duty-cycle value set by PID controller with value of Kp=0.005 Ki=9.75 Kd=0.00000029, the average output voltage is 36. 0067 Volts and stable at the desired setpoint of 36 Volts.